Urban Planning Dealing with Change and Infrastructure - Deppisch, Sonja; Dittmer, Daniel (TeMA - Journal of Land Use, Mobility and Environment, 2015)
<!–[if gte mso 9]> <![endif]–> This paper deals with urban planning and change processes potentially impacting local infrastructure. The overarching theoretical frame is social-ecological resilience thinking and its potential application to as well as implications for urban land-use development. The paper draws its main attention on if this concept can be of use for urban planners dealing with change and urban infrastructure and if a readiness towards its application can be identified. This endeavor is informed by two explorative studies in Germany. One study gains its material from a scenario process with planning practitioners and further urban stakeholders of a medium-sized city. Main topic was how to deal with the challenges of climate change impacts in urban planning and development. The second explorative study reflects research results on the readiness to apply the resilience concept to urban planning dealing with change and local infrastructure in a small community. The scenario process showed that applying social-ecological resilience thinking to urban planning helps to critically reflect so far taken paths in local built infrastructure, to take on an integrated perspective and to develop new and innovative strategies for further land-use development. Nevertheless, such a process requires additional financial as well as human resources and translation exercises. Also, the given path dependency as well as financial constrains are hindering to perceive any leeway in infrastructure development at the political level, so that any real implementation at the moment seems to be out of sight, which is also caused by multi-level dependencies. <!–[if gte mso 9]> Normal 0 21 false false false DE X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>